Gender Equality in the New Millennium: Goal or Gimmick? - ANTROBUS, PEGGY (Caribbean Quarterly, 2006)
At the Millennium Summit in September 2000 the largest gathering of world leaders adopted the UN Millennium Declaration, committing their nations to a new global partnership to reduce extreme poverty and setting out a series of time-bound targets, all with a deadline of 2015, that have become known as the Millennium Development Goals (MDGs). The Millenium Development Goals are now part of an international development framework which many countries in the Caribbean have signed on to. This paper addresses the question of how the Millenium Development Goals can be made to work to promote gender equality and empowerment in the Caribbean Community (CARICOM) region. The analysis here will not be limited to "gender equality and women's empowerment (MDG Goal 3). It will also highlight the gender dimensions of some of the other MDGs that closely related to women's equality and empowerment - as a means and as an outcome. Finally, the analysis and suggestions in relation to strategies "to ensure that gender inequalities are identified and addressed in the MDG monitoring process and in national policy responses from governments" will focus on Caribbean realities. Suggestions are made by drawing on the findings and insights on the linkages between global trends, development strategies (including the macroeconomic policy framework of structural adjustment) and their impact on poor women, and the ways in which we might now approach activist interventions toward the goal of gender equality and women's empowerment.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; caraïbes; cours; discipline; féminisme des caraïbes; féminismes noirs; histoire et politique; pol4022; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences de l'éducation; thématiques

Le mouvement mondial des femmes - Antrobus, Peggy (Enjeux planète, 2007)
Qu'ont en commun des intellectuelles féministes radicales, des groupes de soutien aux femmes victimes de la guerre, des associations de mères ou d''ouvrières? Peu de choses, à première vue. Or, depuis quelques décennies, des femmes de partout travaillent à tisser des liens, organiser des échanges et donner à leurs luttes une structure cohérente. Alors que plusieurs ignorent même son existence, le mouvement des femmes peut aujourd''hui compter sur une expérience, un pouvoir et des réseaux extraordinaires.Ce livre, fruit de décennies de rencontres, de négociations, d'écoute et de réflexion, retrace les origines du mouvement mondial des femmes, l'étudié dans son extrême diversité et invite toutes les citoyennes engagées à dialoguer les unes avec les autres. C'est le message d''une pionnière aux nouvelles générations de militantes. Antrobus redonne au mouvement mondial des femmes la place qui lui revient dans la mouvance altermondialiste et resitue l'action des femmes dans le monde et dans l'histoire. Le mouvement des femmes se trouve aujourd'hui à un carrefour entre la protection de gains acquis de haute lutte et la submersion par la vague de la globalisation.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; droits des femmes*; fem1000; international; justice sociale; militance; mouvements des femmes*; mouvements féministes; participation citoyenne; premier cycle; périodes historiques; thématiques